Global trends in the choice of exchange rate regime - Bleaney, Michael; Tian, Mo; Yin, Lin (Springer, 2016)
The raw data suggest that the global trend towards greater exchange rate flexibility that was evident before 1990 has since stopped. An optimum currency area (OCA) model of exchange rate regime choice is estimated. Four different schemes for classifying exchange rate regime are investigated. Trends in the explanatory variables made little difference to the trend towards greater flexibility before 1990 but have worked against it since, largely because of the reduction in inflation. Underlying preferences are still shifting gradually in the direction of greater flexibility.